Hungarian Monitoring, 8 November 1989 . [Magyar rádiófigyelő], 1989. november 8 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Situation in the GDR - Situation in the FRG, Kohl's summary - Sino-American diplomatic relations - Chirac on aid for Hungarian and Polish economies Domestic Affairs: - Four opposition parties form alliance over referendum - Hungarian and Spanish premiers in talks - Imre Pozsgay holds press conference - Foreign Ministry protests case of Timisoara Calvinist minister László Tőkés at Romanian embassy in Budapest Economy: - Hungarian-South Korean trade relations - Suzuki car production in Hungary Külpolitika: - NDK-helyzet - NSZK-helyzet, Kohl beszámoló - Kínai-amerikai diplomáciai kapcsolatok - Chirac a magyar és lengyel gazdaság támogatásáról Belpolitika: - Négy ellenzéki párt koalíciót alkot a népszavazás kapcsán - Magyar-spanyol kormányfői tárgyalás - Pozsgay Imre sajtótájékoztató - A Külügyminisztérium tiltakozott TŐKÉS László temesvári református lelkész ügyében Románia budapesti nagykövetségénél Gazdaság: - Magyar-dél-koreai kereskedelmi kapcsolatok - SUZUKI autó gyártás ügye